Access for all - Mohd Yaacob, N.; Mohd Ariffin, R. (2001)
We do not see many disabled and elderly persons using the streets, pathways and pedestrian crossings in many Malaysian cities. Reports of the disabled being disadvantaged and sidelined where equal opportunities in education, recreation, employment and commerce, had been highlighted before. The issue of inaccessible or barrier-filled access often originates from discrepancies in the planning, design and building of the built environment that do not cater adequately to the needs of the disabled and elderly persons. The lack of accessibility, erect barriers for the disabled. The frustrations in being immobile, dependent and being patronized while having to cope with day to day living, saps the energy and efficiency away from the disabled user in wanting to have equal opportunities at being successful in life, like everyone else. For example, with the lack of access to better education, many disabled persons have difficulties to pursue further education, and limited opportunities to progress. Depending on the degree and type of impairment and the emphasis on mobility, the limitations are obvious when an able-bodied person would have no problems traveling long distances to work, or work overtime or part-time in order to supplement the high cost of living. Due to rapid urbanization, and the expansion of cities in Malaysia and everywhere else in the world, the disabled person has to live in the cities to survive and get a better life. Many disabled persons are from the low-income group. Hence, the expensive mode of public transport and mobility is the norm for a disabled person, rather than a choice. So, there is actually 'no choice'. I Lack in mobility due to lack of facilities for the disabled and elderly in transportation is further burdened with the lack of access in the built environment, in particular the pedestrian environment.